Surface-treated aluminum material and its manufacturing method

JP7609577B2Active Publication Date: 2025-01-07UACJ CORP

Patent Information

Application Number
JP2020115109
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-02
Publication Date
2025-01-07
Estimated Expiration
2040-07-02

AI Technical Summary

Benefits of technology

【0013】 粘着フィルムならびに樹脂等の他の材料との密着性が優れた表面処理アルミニウム材及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609577000004
    Figure 0007609577000004
  • Figure 0007609577000005
    Figure 0007609577000005
  • Figure 0007609577000001
    Figure 0007609577000001
Patent Text Reader

Abstract

To provide a surface-treated aluminum material with excellent adhesion with other materials.SOLUTION: A surface-treated aluminum material comprises an aluminum material, and an oxide film formed at least in a part on a surface of the aluminum material. When a boundary length and an area of a gap on a surface of the oxide film are L and S, respectively, a degree of irregularity defined by L2 / S×(1 / 4π) is higher than or equal to 2.5.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface-treated pure aluminum material or aluminum alloy material (hereinafter referred to as "aluminum material"), and more particularly to a surface-treated aluminum material. [Background technology]

[0002] Aluminum materials are lightweight and have moderate mechanical properties, as well as excellent aesthetics, electrical conductivity, heat dissipation, corrosion resistance, and recyclability, and are therefore used in a variety of structural components, heat exchange components, containers, packaging, electronic devices, machinery, and the like.

[0003] In many cases, these aluminum materials are surface-treated in part or in whole to impart or improve properties such as corrosion resistance, insulation, adhesion, antibacterial properties, and abrasion resistance.

[0004] In recent years, resource and energy conservation has been promoted, especially in the automobile industry, and when aluminum materials are used for structural members, structural members in which a part or all of the aluminum material is bonded with resin to achieve further weight reduction have been proposed. Since these structural members are used for transportation equipment, they are required to have high adhesion durability in atmospheric and corrosive environments.

[0005] When manufacturing a member in which such an aluminum material is bonded to a resin or a painted member, the surface treatment of the aluminum material is necessary to improve the adhesion between the aluminum material and the resin or coating. For example, Patent Document 1 proposes an alkaline AC electrolysis method as such a surface treatment method. That is, in the method of Patent Document 1, an alkaline solution having a solution temperature of 30 to 90° C. and a pH of 9 to 13 is used, and an AC electrolysis treatment is performed for an electrolysis time of 5 to 60 seconds using a waveform in which the anode peak voltage at the end of electrolysis is 25 to 200 V and the anode peak voltage at the beginning of electrolysis is 0.1 to 25 V. Patent Document 1 states that an aluminum material on which an oxide film having a thickness of 50 to 1000 nm is formed can be obtained.

[0006] In addition, when preparing an aluminum / thermoplastic resin composite in which an aluminum material and a thermoplastic resin are firmly bonded, a chemical treatment method for an aluminum material that utilizes the etching action of an aqueous solution has also been proposed, as in Patent Document 2. That is, in the method of Patent Document 2, an aluminum material is immersed in an aqueous solution having an etching action under appropriate conditions, or these solutions are sprayed onto the surface of the aluminum material to form multiple recesses on the surface of the aluminum material, and among the multiple recesses, a recess 1 having a maximum pore diameter of 10 μm or more and a maximum depth of 5 μm or more in a cross section along the maximum pore diameter length is designated as a specific recess, and an aluminum material having a total perimeter L (mm) of the specific recesses present in any 1 mm square on the roughened surface of 0.10 mm≦L≦0.35 mm is composited with a thermoplastic resin having an apparent modulus of elasticity E=S / ε(MPa / %) of 0.0050≦E≦0.0380, where S (MPa) is the tensile breaking strength, and ε (%) is the tensile breaking elongation.

[0007] Furthermore, the method of Patent Document 3 describes that by forming an anodized film on an aluminum or aluminum alloy plate, in which the area of ​​regions having pores with diameters of 10 nm or more accounts for 75% or more of the total area and the film has a thickness of 0.1 to 1 μm, a material can be obtained in which the thermoplastic resin film will not peel off from the aluminum or aluminum alloy plate, even if a drawing or drawing and ironing process is performed under severe conditions such as a drawing ratio of 2.5 or more, after forming a thermoplastic resin film on the anodized film.

[0008] In the above-mentioned conventional technology, the surface treatment by AC electrolysis of Patent Document 1 has a problem with electrolysis efficiency because only about half of the electrolysis current is used for generating an oxide film.

[0009] Furthermore, in the method of forming anodized aluminum on an aluminum surface as described in Patent Document 3, the tape peel strength measured using an adhesive tape was insufficient, and further improvement was required. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2015-25281 A [Patent Document 2] JP 2015-102608 A [Patent Document 3] Japanese Patent Application Publication No. 11-207860 Summary of the Invention [Problem to be solved by the invention]

[0011] As a result of extensive investigations aimed at solving the above problems, the inventors discovered that by simultaneously generating an oxide film and chemically dissolving the film, oxides having irregular morphology are formed on the surface of an aluminum material, and the anchoring effect of the oxide film is enhanced, resulting in high adhesion between the aluminum material and other materials. [Means for solving the problem]

[0012] That is, the gist and configuration of the present invention are as follows. [1] A surface-treated aluminum material having an aluminum material and an oxide film formed on at least a part of a surface of the aluminum material, When the perimeter of the void on the surface of the oxide film is L and the area is S, L 2 A surface-treated aluminum material in which the void irregularity degree defined as / S × (1 / 4π) is 2.5 or more. [2] The surface-treated aluminum material according to the above [1], wherein the voids have a diameter of 15 to 65 nm in terms of an equivalent circle diameter. [3] The surface-treated aluminum material according to the above [1] or [2], wherein the area occupancy of voids on the surface of the oxide film is 10 to 60%. [4] The surface-treated aluminum material according to any one of [1] to [3] above, further comprising a resin layer on the surface of the oxide film. [5] The oxide film has a barrier-type anodic oxide film layer formed on at least a part of the surface of the aluminum material, and an aluminum oxide film layer formed on the barrier-type anodic oxide film layer, The surface-treated aluminum material according to any one of [1] to [4] above, wherein the voids are located on the surface of the aluminum oxide coating layer. [6] A method for producing a surface-treated aluminum material according to any one of [1] to [5] above, An acid or alkaline aqueous solution with a temperature of 30 to 90°C is used as the electrolyte. Current density is 10A / m 2 More than 3000A / m 2 A method for producing a surface-treated aluminum material, comprising the steps of: subjecting an aluminum material to an electrolytic treatment so as to form the oxide film; Effect of the Invention

[0013] It is possible to provide a surface-treated aluminum material having excellent adhesion to other materials such as adhesive films and resins, and a method for producing the same. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic diagram of a surface-treated aluminum material according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a front view showing an electrolysis apparatus used in a method for producing a surface-treated aluminum material according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The surface-treated aluminum material of the present invention will be described in detail below. A. Aluminum material Pure aluminum or an aluminum alloy can be used as the aluminum material (for example, 2 in FIG. 1 described later) constituting the surface-treated aluminum material according to one embodiment of the present invention. There is no particular limitation on the components of the aluminum alloy, and various alloys including those specified by JIS can be used. There is no particular limitation on the shape of the aluminum material, and it can be a flat plate, a bar of any cross-sectional shape, a wire, a cylinder, etc., and there is no particular limitation on the manufacturing method of these shapes, and various methods that can stably form an oxide film can be suitably used.

[0016] B. Oxide film Fig. 1 is a schematic diagram of a surface-treated aluminum material according to one embodiment of the present invention. As shown in Fig. 1, in the surface-treated aluminum material according to one embodiment of the present invention, an oxide film 1 is formed on at least a portion of the surface of an aluminum material 2 (for example, at least one of two opposing faces in the case of a flat aluminum material). In the example of Fig. 1, this oxide film 1 is composed of an aluminum oxide film layer 3 formed on the surface side of the oxide film and having voids 31, and a barrier-type anodic oxide film layer 4 formed on the aluminum material 2 side.

[0017] B-1. About voids As shown in Fig. 1, the aluminum oxide coating layer 3 has voids 31, which are small holes extending inward from the surface. On the surface of the aluminum oxide coating layer 3, the openings of all the small holes that exist in the surface area without taking unevenness into consideration (when the surface of the aluminum oxide coating layer 3 is rectangular, the surface area is calculated by the length x width of the rectangle) are defined as voids 31. In the present invention, the unevenness of these voids 31 is 2.5 or more. Here, the "unevenness" refers to the ratio of the perimeter of the voids 31 when the surface of the oxide coating layer 1 is viewed in a direction perpendicular to the surface to the surface, where L is the perimeter and S is the area of ​​the voids 31. 2 / S×(1 / 4π). Specific methods for measuring L and S will be described later. If the unevenness is less than 2.5, the adhesion between the oxide film 1 and the object to be joined is reduced, and for example, when the surface of the oxide film 1 is further covered with an object to be joined, such as a resin layer, the anchor effect in the joining between the oxide film 1 and the object to be joined is insufficient. Therefore, when an adhesive is used to join the oxide film 1 and the object to be joined, destruction occurs at the interface between the outermost surface of the oxide film 1 and the adhesive. The unevenness is preferably 2.5 to 10, more preferably 2.5 to 8, and even more preferably 2.5 to 6. By having the unevenness within the above range, the oxide film 1 can have better adhesion to the object to be joined provided thereon.

[0018] When observed from a direction perpendicular to the surface of the oxide film 1, the voids 31 have various shapes, such as circles, ellipses, rectangles, polygons, and irregular shapes. When the perimeter of such a void is equal to the perimeter of a perfect circle, the diameter of the perfect circle is defined as the equivalent circle diameter. For example, if the shape of the void is a perfect circle, the perimeter is naturally the same as that of a perfect circle, so the diameter is defined as the equivalent circle diameter. Alternatively, if the shape of the void is a polygon, a perfect circle equal to the perimeter is defined, and the diameter of the perfect circle is defined as the equivalent circle diameter.

[0019] The diameter of the voids is preferably 15 nm to 65 nm, more preferably 25 nm to 60 nm, calculated as the equivalent circle diameter. When the equivalent circle diameter is 15 nm or more, the anchor effect in the bonding between the oxide film and the bonded body such as a resin is good, and the adhesion between the oxide film and the bonded body provided thereon can be excellent. On the other hand, when the equivalent circle diameter is 65 nm or less, a hook structure for exerting the anchor effect is suitably formed, and therefore the adhesion can be excellent.

[0020] Also, on the surface of the oxide film (for example, the aluminum oxide film layer 3), the ratio of the total area of ​​all the voids 31 to the surface area (of the surface where the voids exist) not considering unevenness is defined as the void area ratio. For example, when the surface where the voids exist is a rectangle, the ratio of the total area of ​​all the voids 31 to the surface area calculated by the length and width of the rectangle is defined as the void area ratio. In the present invention, the void area ratio is preferably 10 to 60%, and more preferably 15 to 55%. When this area ratio is 10% or more, the anchor effect in the bonding between the oxide film and the bonded body is good, and the adhesion can be excellent. When this area ratio is 60% or less, the oxide film itself is less likely to undergo cohesive failure, and the adhesion between the oxide film and the bonded body can be excellent.

[0021] In FIG. 1, the void 31 does not penetrate the barrier type anodic oxide coating layer 4 in the depth direction, but the void 31 may penetrate the barrier type anodic oxide coating layer 4. The position of the tip of the void 31 on the opposite side to the surface of the aluminum oxide coating layer 3 in the depth direction is not particularly limited. However, the position of the tip is preferably 20 to 100% of the thickness of the oxide coating 1 from the surface of the oxide coating 1, and more preferably 40 to 95%. If it is 20% or more, the anchor effect in the bonding between the oxide coating and the bonded body is good, and the adhesion can be excellent. The surface-treated aluminum material of one embodiment further has a resin layer on the surface of the oxide coating. In this case, the oxide coating and the resin layer can have good adhesion due to the anchor effect of the oxide coating surface as described above. The material constituting the resin layer is not particularly limited, but for example, epoxy resin, ABS resin, fluororesin, etc. can be used.

[0022] C. Manufacturing method for surface-treated aluminum materials Hereinafter, a method for producing a surface-treated aluminum material according to one embodiment of the present invention will be described.

[0023] C-1. Electrode One method for producing the surface-treated aluminum material of the present invention is to form an oxide film by electrolytic treatment under specified conditions using the aluminum material to be surface-treated as one electrode and the other as a counter electrode.

[0024] In one embodiment of the present invention, the shapes of the aluminum material to be electrolytically treated and the counter electrode are not particularly limited. For example, a plate-shaped counter electrode is preferably used for a flat aluminum material in order to make the distance between the counter electrode uniform and to form a stable electrolytic oxide film. FIG. 2 is a schematic diagram showing a state in which electrolytic treatment is performed under predetermined conditions using an aluminum material as one electrode and the other counter electrode. As shown in FIG. 2, wired counter electrode plates 5 and 6 are prepared, and both surfaces of an aluminum plate 7 to be surface-treated can be placed between these two counter electrode plates so that they are parallel to the surfaces of the counter electrode plates 5 and 6. It is preferable to perform electrolytic treatment with both electrodes stationary, with the dimensions of the surfaces of the opposing aluminum material 7 and the counter electrode being approximately the same. In addition, when only one surface of the aluminum plate 7 to be surface-treated is to be treated, it is also possible to treat only one surface of the aluminum material 7 (the surface on the left side of the aluminum material in the figure) by sticking an insulating film to one side of the aluminum material after turning off the counter electrode plate connection switch 10.

[0025] One of the pair of electrodes used in the electrolytic treatment is an aluminum material to be surface-treated by the electrolytic treatment. As the other counter electrode, a known electrode such as a graphite, aluminum, gold, or titanium electrode can be used, but it is necessary to use a material that does not deteriorate due to the components of the electrolytic solution or the temperature, has excellent electrical conductivity, and does not cause an electrochemical reaction by itself. From these points of view, a graphite electrode is preferably used as the counter electrode. This is because the graphite electrode is chemically stable, inexpensive, and easily available.

[0026] C-2. Electrolytic treatment conditions The electrolytic treatment conditions were as follows: the aluminum electrode and counter electrode were used; an acid or alkaline aqueous solution with a temperature of 30 to 90°C was used as the electrolytic solution; and the current density was 10 A / m 2 More than 3000A / m 2 An oxide film can be formed by electrolyzing an aluminum material so that the current density is 10 A / m or less. The current waveform during electrolysis is not limited to AC, DC, or AC / DC superimposed application, but from the viewpoint of electrolysis efficiency, it is preferable to use the aluminum material as the anode and to use a current density of 10 A / m or less. 2 More than 3000A / m 2 Less than or equal to 50A / m 2 More than 2000A / m 2 Less than 100 A / m, more preferably 2 More than 1000A / m 2 In the case of AC or AC-DC superimposed application, the current density is defined as the current value when the amount of electricity flowing per unit area is the largest, divided by the reaction area, and the current density is preferably 10 A / m 2 More than 3000A / m 2 Less than or equal to 50A / m 2 More than 2000A / m 2 Less than 100 A / m, more preferably 2 More than 1000A / m 2 It is recommended to use a current waveform such that:

[0027] In one embodiment of the present invention, the aqueous solution using an acid or alkaline aqueous solution as the electrolyte solution may be an aqueous solution containing an inorganic acid such as sulfuric acid, phosphoric acid, arsenic acid, selenic acid, etc.; an organic acid such as oxalic acid, malonic acid, etidronic acid, etc.; a cyclic oxocarboxylic acid such as squaric acid, rhodizonic acid, etc.; a borate such as sodium tetraborate, etc.; a phosphate such as sodium phosphate, sodium hydrogen phosphate, sodium pyrophosphate, potassium pyrophosphate, and sodium metaphosphate, etc.; an alkali metal hydroxide such as sodium hydroxide and potassium hydroxide, etc.; a carbonate such as sodium carbonate, sodium hydrogen carbonate, and potassium carbonate, etc.; an ammonium-containing compound such as ammonium hydroxide and ammonium borate, etc.; or a mixture thereof. Usually, the concentration of these aqueous solutions is 1×10-4 ~12 moles / liter, preferably 1×10 -2 The concentration is 1 mol / L or less. Note that a surfactant, a chelating agent, or the like may be added to these aqueous solutions in order to improve the cleanliness of the aluminum material surface.

[0028] The temperature of the electrolytic solution used in one embodiment of the present invention is preferably 30 to 90°C, more preferably 35 to 85°C. When the temperature of the electrolytic solution is 30°C or higher, the etching power is suitable, so that the area occupancy rate of the voids on the oxide film surface is large, and the circle equivalent diameter of the voids can also be made sufficient. On the other hand, when the temperature of the electrolytic solution is 90°C or lower, the etching power is suitable, so that cohesive failure of the oxide film is not induced. In addition, the electrolysis time is preferably 5 to 750 seconds, more preferably 60 to 600 seconds. When the electrolysis time is 5 seconds or more, the oxide film can be sufficiently formed. As a result, voids with a sufficient degree of unevenness can be formed. On the other hand, when the electrolysis time is 750 seconds or less, the oxide film does not become too thick or dissolve, and there is no risk of the oxide film undergoing cohesive failure. In addition, the productivity of the surface-treated aluminum material is also improved.

[0029] D. Measurement methods for unevenness, equivalent circle diameter and area occupancy rate In the present invention, the unevenness, circle equivalent diameter, and area ratio of the voids in the oxide film having the voids are preferably measured by surface observation using a field emission scanning electron microscope (FE-SEM, SU-8230, Hitachi High-Technologies Corporation) and analysis using image analysis software WinRoof 2015 (Mitani Shoji Co., Ltd., ver. 2.1.0). In SEM observation, the surface of the sample may be coated with a conductive layer of platinum, gold, osmium, carbon, etc. to prevent charge-up. Specifically, a secondary electron image of a sample of a surface-treated aluminum material photographed at an accelerating voltage of 10 kV and an observation magnification of 100,000 times is imported into image analysis software, and the voids observed on the surface of the oxide film are binarized to perform image analysis. In the image analysis, binarization processing is performed so that the voids in the oxide film are included in the target range, and then closing processing is performed twice to remove isolated points. Then, shape measurement was selected from the measurement menu, and the measurement items were selected as unevenness, circle equivalent diameter, and area ratio, and the unevenness, circle equivalent diameter, and area ratio were measured. The average values ​​of the measured unevenness and circle equivalent diameter were calculated, and these were defined as the unevenness and circle equivalent diameter of each surface. This allows the unevenness and circle equivalent diameter of all voids on the surface of the oxide film to be measured at each location. In addition, the area occupancy rate of the voids at each location, which indicates the ratio of the sum of all void areas to the total area not taking unevenness into account, can be obtained from the sum of the area rates. The unevenness, circle equivalent diameter, and area occupancy rate of the voids are as defined above. EXAMPLES

[0030] The present invention will be described in detail below based on examples. Note that the present invention is not limited to the examples shown below, and the configuration can be appropriately changed without departing from the spirit of the present invention.

[0031] (Examples 1 to 8 and Comparative Examples 1 to 5) A high-purity aluminum plate (aluminum material) having a purity of 99.9% or more and a size of 100 mm long x 50 mm wide x 0.4 mm thick was used as the aluminum material to be electrolytically treated. This aluminum plate was used as one electrode, and a flat graphite electrode having a size of 200 mm long x 90 mm wide x 2.5 cm thick was used as the counter electrode. As shown in FIG. 2, between the two graphite plate counter electrodes 5 and 6 connected to each other and facing each other, both sides of the aluminum plate electrode 7 were arranged parallel to the opposing graphite plate counter electrodes 5 and 6, respectively, and the aluminum plate was electrolytically treated. By this electrolytic treatment, an oxide film consisting of an aluminum oxide film layer on the front side and a barrier-type anodic oxide film layer on the aluminum plate side was formed on both sides of the aluminum plate electrode 7 facing the two graphite counter electrodes 5 and 6, respectively.

[0032] The electrolytic solution used in the electrolytic treatment was an aqueous solution containing oxalic acid as a main component. The electrolyte concentration of this aqueous solution was 0.3 mol / L, as shown in Table 1. An aluminum plate and both counter electrodes were placed in an electrolytic cell containing the electrolytic solution, and a direct current electrolytic treatment was carried out under the conditions shown in Table 1. The vertical directions of the aluminum plate and the graphite counter electrode coincided with the depth direction of the electrolytic cell.

[0033] [Table 1]

[0034] As described above, in Examples 1 to 8 and Comparative Examples 1 to 5, the counter electrode connection switch 10 in Fig. 2 was connected to form an oxide film on both sides of the aluminum material. After the electrolytic treatment, the aluminum material was quickly removed from the electrolytic cell, washed with pure water, air-dried with a blower, and then naturally dried in the air at room temperature.

[0035] The samples of the surface-treated aluminum material prepared as described above were subjected to the following measurements and evaluations.

[0036] [Measurement of the unevenness, circle equivalent diameter and area occupancy rate of voids when observing the surface of an aluminum oxide film layer] For the surface-treated aluminum material samples prepared as described above, surface observation was performed using FE-SEM and image analysis was performed using image analysis software WinRoof 2015 (Mitani Shoji Co., Ltd. ver.2.1.0) to measure the unevenness, circle equivalent diameter, and area occupancy rate of the voids in the aluminum oxide film layer. First, a surface secondary electron image (accelerating voltage 10 kV) was taken using FE-SEM with an observation field of 2.5 μm × 0.9 μm, and image analysis was performed using WinRoof 2015. The results are shown in Table 2. Details of the surface observation and image analysis are as described above.

[0037] [Table 2]

[0038] [Adhesion evaluation of oxide film] A pressure-sensitive adhesive tape (No. 29) manufactured by Nitto Denko Corporation was applied to the surface-treated aluminum material samples of each example prepared as described above, and the tape peel strength was measured by peeling the tape at a speed of 150 mm / min using a 90° peel tester (TE-3001-S manufactured by Tester Sangyo Co., Ltd.). The load cell used for the measurement was LRU-50N manufactured by Nippon Tokushu Sokki Co., Ltd. The measurement results of the tape peel strength are shown in Table 3. A peel strength of 5 N / cm or more and less than 6.5 N / cm was marked as "○", 6.5 N / cm or more was marked as "◎", and the rest was marked as "×". ○ and ◎ were judged as pass, and × was judged as fail.

[0039] [Table 3]

[0040] As shown in Table 3, in Examples 1 to 8, the average unevenness of the voids in the aluminum oxide film layer was 2.5 or more, so that the adhesion between the oxide film and the adhesive film was good and the adhesion was acceptable.

[0041] In contrast, as shown in Table 3, no surface-treated aluminum materials having an oxide film structure according to the present invention were obtained in Comparative Examples 1 to 5. As a result, the adhesion between the oxide film and the adhesive film was insufficient, and the adhesion was unacceptable.

[0042] Specifically, in Comparative Example 1, the temperature of the electrolytic solution in the electrolytic treatment was too low, resulting in a weak etching power, an insufficient area occupancy rate of the voids in the aluminum oxide coating layer, and a low degree of unevenness, which resulted in the adhesion being unacceptable.

[0043] In Comparative Example 2, the electrolytic treatment was performed for a long time using a high-temperature solution at a high current density, which resulted in excessive etching and cohesive failure of the aluminum oxide film layer itself, resulting in a failure in adhesion.

[0044] In Comparative Example 3, the temperature of the electrolytic solution in the electrolytic treatment was low and the current density was also low, resulting in a weak etching power, an insufficient area occupancy rate of the voids in the aluminum oxide coating layer, and a low unevenness. As a result, the adhesion was unacceptable.

[0045] In Comparative Example 4, the temperature of the electrolytic solution in the electrolytic treatment was low, similar to Comparative Example 3, so that the etching power was weak, the area occupancy rate of the voids in the aluminum oxide coating layer was insufficient, and the unevenness was also low. Therefore, the adhesion was unacceptable.

[0046] In Comparative Example 5, the etching of the voids was insufficient because the electrolysis time was short relative to the current density in the electrolysis treatment, and many fine pores were generated, resulting in an insufficient unevenness. As a result, the adhesion was unacceptable. [Industrial Applicability]

[0047] According to the present invention, it is possible to obtain a surface-treated aluminum material that has excellent adhesion to objects to be joined, such as adhesive tape, resin, etc. As a result, the surface-treated aluminum material according to the present invention is suitably used for aluminum / resin joined members and resin-coated aluminum materials, which require resin adhesion to aluminum materials. [Explanation of symbols]

[0048] 1. Oxide film 2. Aluminum material 3 Aluminum oxide layer 4. Barrier-type anodic oxide film layer 5, 6 Counter electrode plate 7 Aluminum plate 31 void

Claims

1. A surface-treated aluminum material having an aluminum material and an oxide film formed on at least a part of a surface of the aluminum material, When the perimeter of the void on the surface of the oxide film is L and the area is S, L 2 The unevenness of the gap defined by / S×(1 / 4π) is 2.5 or more, The surface-treated aluminum material has a void diameter of 25 to 65 nm in terms of a circle-equivalent diameter.

2. 2. The surface-treated aluminum material according to claim 1, wherein an area occupancy rate of voids on the surface of the oxide film is 10 to 60%.

3. 3. The surface-treated aluminum material according to claim 1, further comprising a resin layer on a surface of the oxide film.

4. the oxide film has a barrier-type anodic oxide film layer formed on at least a part of a surface of the aluminum material, and an aluminum oxide film layer formed on the barrier-type anodic oxide film layer, The surface-treated aluminum material according to claim 1 , wherein the voids are located on a surface of the aluminum oxide coating layer.

5. A method for producing a surface-treated aluminum material according to any one of claims 1 to 4, An acidic aqueous solution with a temperature of 30 to 90°C is used as the electrolyte. Current density is 10 A / m 2 More than 3000A / m 2 A method for producing a surface-treated aluminum material, comprising the steps of: subjecting an aluminum material to an electrolytic treatment so as to form the oxide film;

Citation Information

Patent Citations

  • Mold for pressure forming

    JP1982004716A

  • Thermoplastic resin-clad aluminum or aluminum alloy plate, and manufacture thereof

    JP1999207860A

  • Aluminum material and its manufacturing method

    JP2010000679A

  • Bit device of shield machine

    JP2015025281A

  • Method for manufacturing photomask, photomask, method for transferring pattern, and method for manufacturing display device

    JP2015102608A

Cited By

  • Surface-treated aluminum material and method for producing the same

    US12571121B2